2015
DOI: 10.3390/ijms161226212
|View full text |Cite
|
Sign up to set email alerts
|

Tudor-SN Regulates Milk Synthesis and Proliferation of Bovine Mammary Epithelial Cells

Abstract: Tudor staphylococcal nuclease (Tudor-SN) is a highly conserved and ubiquitously expressed multifunctional protein, related to multiple and diverse cell type- and species-specific cellular processes. Studies have shown that Tudor-SN is mainly expressed in secretory cells, however knowledge of its role is limited. In our previous work, we found that the protein level of Tudor-SN was upregulated in the nucleus of bovine mammary epithelial cells (BMEC). In this study, we assessed the role of Tudor-SN in milk synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…In addition, we found that miR-139 inhibited not only the activity of downstream signaling molecules of the GHR and IGF1R pathways, but also the total protein levels of key molecules of these pathways. This phenomenon has also been found by others [ 24 , 35 ]. These observations suggest that miR-139 likely inhibits synthesis of β-casein through GHR and IGF1R signaling in BMECs.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we found that miR-139 inhibited not only the activity of downstream signaling molecules of the GHR and IGF1R pathways, but also the total protein levels of key molecules of these pathways. This phenomenon has also been found by others [ 24 , 35 ]. These observations suggest that miR-139 likely inhibits synthesis of β-casein through GHR and IGF1R signaling in BMECs.…”
Section: Discussionsupporting
confidence: 88%
“…Primary BMECs were separated and cultured according to previously reported methods (Ao et al, ; L. Wang et al, ). BMECs were cultured in glass cell culture plates in an incubator at 37°C in the presence of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…), amino acids (Met, Leu, etc. ), glucose, and fatty acids promote milk fat synthesis through the SREBP-1c pathway, but the detailed mechanism is still unclear (Ao et al, 2015;Zhang et al, 2018).…”
mentioning
confidence: 99%
“…Then we performed western blot analysis to determine whether the phosphorylation of the Tudor‐SN affected the expression of the milk proteins and mTOR signaling pathway which has been confirmed to be a positive regulator to control milk protein synthesis and cell proliferation of BMECs (Wang et al, ; Zhang et al, ). Furthermore, Tudor‐SN has been verified to positively regulate milk synthesis through mTOR signaling pathway (Ao et al, ). Therefore, mTOR and β‐casein were used as the milk protein synthesis marker.…”
Section: Resultsmentioning
confidence: 99%